Chemical component separation: a systematic review and meta-analysis of botulinum toxin for management of ventral hernia. Issue 5 (3rd September 2017) - Weissler, Jason M.; Lanni, Michael A.; Tecce, Michael G.; Carney, Martin J.; Shubinets, Valeriy; Fischer, John P.
Abstract: Background: Ventral hernia represents a surgical challenge plagued by high morbidity and recurrence rates. Primary closure of challenging hernias is often prohibited by severe lateral retraction and tension of the abdominal wall musculature. Botulinum toxin injections have recently been identified as a potential pre-operative means to counteract abdominal wall tension, reduce hernia size, and facilitate fascial closure during hernia repair. This systematic review and meta-analysis reviews outcomes associated with botulinum toxin injections in the setting of ventral hernia, and demonstrates an opportunity to leverage this mainstream aesthetic product for use in abdominal wall reconstruction. Methods: A literature review was conducted according to PRISMA guidelines using MeSH terms 'ventral hernia', 'herniorrhaphy', 'hernia repair', and 'botulinum toxins'. Relevant studies reporting pre- and postinjection data were included. Outcomes of interest included changes in hernia defect width and lateral abdominal muscle length, recurrence, complications, and patient follow-up. Qualitative findings were also considered to help demonstrate valuable themes across the literature. Results: Of 133 results, 12 were included for qualitative review and three for quantitative analysis. Meta-analysis revealed significant hernia width reduction (mean = 5.79 cm; n  = 29; p  < 0.001) and lateral abdominal wall muscular lengthening (mean = 3.33 cm; n  = 44; p  < 0.001) following botulinum injections. Mean length of follow-up was 24.7 months (range = 9–49). Conclusions: Botulinum toxin injections offer tremendous potential in ventral hernia management by reducing hernia width and lengthening abdominal wall muscles prior to repair. Although further studies are needed, there is a significant opportunity to bridge the knowledge gap in preoperative practice measures for ventral hernia risk reduction.